Analysis of Coastline Changes and Water Current Circulation Patterns in Batam City, Riau Islands Province - Nainggolan, Robby; Mubarak, Mubarak; Nursyirwani, Nursyirwani (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2025)
Environmental damage is caused by coastal reclamation to advance the economic sector in Batam City. Reclamation can cause changes in the coastline of Batam City. This study aims to determine the extent of changes in the coastline that occurred in Batam City from 2003 to 2023 and to understand the pattern of ocean current circulation in Batam City before reclamation in 2003 and after reclamation in 2023. This study was conducted in January 2024. The method used for data analysis to observe changes in the coastline is the Digital Shoreline Analysis System. Numerical models available in the MIKE21 software to model water circulation in estuary beaches. The study results show that land additions dominated changes in the coastline of Batam City from 2003 to 2023. The sub-district with the most significant addition was Bengkong, with an addition of 816.58 m and an addition rate of 39.79 m/year, followed by Nongsa, with an addition of 279.05 m and an accretion rate of 13.59 m/year. The flow pattern during the ebb and flow before reclamation had a maximum speed of 0.27 m/s, while after reclamation, the maximum current speed increased to 0.33 m/s. It can be concluded that the progression of the coastline primarily drove the changes in Batam City's coastline from 2003 to 2023. Meanwhile, the increasing current speed can reach 0.33 m/s